EFL Students’ Academic Buoyancy: Does Academic Motivation and Interest Matter? - Xu, Xin; Wang, Bin (Frontiers in Psychology, 2022)
EFL students’ academic buoyancy is of substantial importance since it makes the world of difference in the amount of motivation students can experience throughout their academic studies. Even though several studies have been conducted regarding the role of motivation and interests experienced by students, a few studies have been done on the association between students’ academic buoyancy and their motivation and interests in EFL contexts; therefore, it seems extremely significant to carry out such a study to examine the link between these two variables. To do this, firstly, both variables of this review study are defined. Then, the relationship between EFL learners’ academic buoyancy and their motivation and interests is discussed. Finally, the implications of this present study and also suggestions for further studies are put forward.